Retrospective Analysis of 55 Patients With Colorectal Injuries - Bülbüller, Nurullah; Doğru, Osman; Kırkıl, Cüneyt; Ayten, Refik; İlhan, Yavuz Selim (Fırat University, 2003)
Aim: The retrospective investigation of patients who were treated in our clinic for colon injury. Materials and method: Fifty-five patients who were followed for colon injury in General Surgery Department of Firat University Medicine Faculty between September 1994 and June 2001 were examined, retrospectively. Etiological factors of colon injuries, applied surgical procedures, complications and mortalities were detected. Results: Of 55 patients who were followed for colon injury, 9 patients were female (%16,3) and 46 patients were male (%80,7) with 68,7 (range from 16 to 80) median years old. The most common cause of colon injury was gunshot wound (%69,0) in these cases. 24 primary repair (%43,63), 28 resection + stoma (%50,9) and 2 resection + anastomosis (%3,63) were performed for these patients. Various complications came out in 22 patients (%40,0). Four patients (%7,27) of these patients who were followed for colon injury were die.

Amaç: Kolon yaralanması nedeniyle kliniğimizde tedavi edilen hastaların retrospektif incelenmesi. Gereç ve yöntem: Eylül 1994 - Haziran 2001 tarihleri arasında Fırat Üniversitesi Tıp Fakültesi Genel Cerrahi Kliniği'nde kolon yaralanması nedeni ile takip edilen 55 hasta retrospektif olarak incelendi. Kolon yaralanmalarının etyolojik nedenleri, uygulanan cerrahi prosedürler, gelişen komplikasyonlar ve mortaliteler tespit edildi. Bulgular: Kolon yaralanması ile takip edilen 55 hastanın 9'u kadın (%16,3) 46'sı erkek (%80,7) olup ortalama yaş 68,7 (16-80) idi. Bu vakalarda kolon yaralanmasının en sık nedeni ateşli silah yaralanması idi (%69,0). Vakaların 24'üne (%43,63) primer tamir, 28'ine (%50,9) rezeksiyon + stoma ve 2'sine (%3,63) rezeksiyon + anastomoz uygulandı. 22 (%40) hastamızda çeşitli komplikasyonlar gelişti. Kolon yaralanması ile takip ettiğimiz bu hastalardan dördü (%7,27) öldü.
Kolorektal Yaralanmalı 55 Hastanın Retrospektif Analizi